Etiological profile of short stature in rural Rajasthan - Singh, Ashwini; Masand, Rupesh; Verma, Chaman Ram; Khinchi, Yograj (Indian Journal of Child Health, 2021)
Background: Short stature is one of the most common referrals to pediatric endocrinology clinics. Approximately 3% of children in any population are found to be short. Aim: This study aims to determine the etiology of short stature and their frequency of occurrence in 2–18 years old rural pediatric population and to classify the patients with short stature using anthropometric measurements. Materials and Methods: A total of 400 patients (age: 2–18 years) were diagnosed with short stature and admitted in pediatric ward. After meticulous history collection and complete physical examination, relevant investigations were performed in all the study subjects. Appropriate statistical analysis was carried out with the collected data. Results: Out of 400 study subjects, 70.50% were boys (male: female=2.33:1). Majority (n=241, 60.5%) of the affected children were in the age group of 2–<6 years and 7–<10 years. Of the 400 study subjects, 95% of cases (n=380) were classified as having proportionate short stature and the rest (n=20, 5%) had disproportionate short stature. Undernutrition (n=117, 29.25%) and familial short stature (n=90, 22.50%) were the leading causes of short stature. Conclusion: The current study helped to determine the etiological profile of short stature in children of adjoining rural population and in devising appropriate strategies for management and prevention.